An iterative spherical mean value method for background field removal in MRI. Issue 4 (19th November 2013) - Wen, Yan; Zhou, Dong; Liu, Tian; Spincemaille, Pascal; Wang, Yi
<x xml:space="preserve">Abstract</x> Purpose The sophisticated harmonic artifact reduction for phase data (SHARP) method has been proposed for the removal of background field in MRI phase data. It relies on the spherical mean value (SMV) property of harmonic functions, and its accuracy depends on the radius of the sphere used for computing the SMV and truncation threshold needed for deconvolution. The goal of this study was to develop an alternative SMV‐based background field removal method with reduced dependences on these parameters. Methods The proposed background field removal method, termed iterative SMV (iSMV), consists of applying the SMV operation repeatedly on the field map. It was validated in a phantom and in vivo brain data of five healthy volunteers. Results The iSMV method demonstrates accurate background field removal in the phantom. Compared with SHARP, the iSMV method shows a significantly reduced dependence on the SMV radius both in phantom and in human data. Because a smaller radius can be chosen, the iSMV method allows retaining a larger part of the region of interest compared with SHARP. Conclusion The iSMV method is an effective background field removal method with a reduced dependence on method parameters. Magn Reson Med 72:1065–1071, 2014. © 2013 Wiley Periodicals, Inc.